“Smelling and Tasting” Parkinson's Disease: Using Senses to Improve the Knowledge of the Disease - Oppo, Valentina; Melis, Marta; Melis, Melania; Tomassini Barbarossa, Iole; Cossu, Giovanni (Frontiers in Aging Neuroscience, 2020)
Among non-motor manifestations of Parkinson’s Disease (PD), peripheral, sensory symptoms are particularly relevant. Smell dysfunction starts very early and frequently precedes the PD motor symptoms by years (being often a cue to the diagnosis). Moreover, olfactory system could be, together with gut, one of those peripheral sites where PD pathology first develops. Unlike smell loss, the relationship between PD and taste impairment is far less established. It can start early in the course of the disease but more frequently appears in advanced stages, in parallel with the advent of MCI, likely reflecting cortical involvement. Among PD patients has been demonstrated an increase in the frequency of the non-tasters for PROP (prototypical gustatory stimulus, 6- n-propylthiouracil), a genetically determined bitter taste which is mediated by TAS2RS38 receptor, and a significant increase of the recessive non-testing variant of this receptor. TAS2R38 receptors are expressed also in other tissues, such as in the epithelia of the gut and nasal cavities, where they can influence epithelial immunity ad its interaction with microbiota. Those pieces of evidence​ suggest that not only systematic assessment of taste and smell can be of a remarkable help for clinicians in the early diagnosis, but also that understanding the mechanisms of sensory involvement in PD could increase the knowledge of the pathophysiology of the disease.